Development of Kipas MATHIC Media to Improve Concept Understanding Ability on Trigonometry Material - Adellia Tri Rahayu; Deria Azka Nurul Fathya; Hanayuki Alya; Intan Amalia; Budi Mulyono; Elsa Susanti; Meryansumayeka; Zulkardi (Universitas Sriwijaya, 2025)
This study aims to develop teaching methods that are effective, supportive, and efficient in enhancing students' understanding of mathematical concepts. The research followed the ADDIE development model, which consists of five phases: analysis, design, development, implementation, and evaluation. The study was conducted in response to students' difficulties in understanding trigonometric concepts and recent advancements in educational media identified by researchers. The feasibility and usability of the instructional tool was assessed by both teachers and students. Its validity was evaluated by involving media and content experts. A descriptive analysis was then performed on data collected through observations and interviews conducted throughout the research process. The results of the validity assessment showed scores of 89.29% from content experts and 80.58% from media experts, indicating that the instructional tool is highly suitable for classroom use. The evaluation form revealed scores of 90% from teachers and 78.72% from students, suggesting that the tool is considered very practical. Furthermore, an analysis of student performance demonstrated that Kipas MATHIC effectively enhances students’ understanding of trigonometric concepts.